Digital anti-aliasing trapezoidal recursively separable image processing filter with resizable scanning multi-element aperture - A. V. Kamenskiy; K. A. Rylov; N. Borodina (Омский научный вестник)
The development of television systems is an important factor for many industries involved in the acquisition, processing, storage and transmission of images. Today, an urgent task in the use of such systems is to improve the quality of images obtained using digital photo and video cameras. To solve this problem, digital recursive-separable smoothing filters can be used. The paper describes the process of operation of the algorithm for changing the size of the scanning multi-element aperture of a smoothing trapezoidal recursive-separable filter for digital image processing. The results of evaluating its performance relative to the same algorithm implemented through classical two-dimensional convolution for various sizes of test images are presented. The influence of the aperture size of the developed filter on the change in the signal-to-noise ratio is assessed. The algorithm is implemented in the MATLAB computing environment.